Analisis Pengaruh Rasio Kesehatan Bank terhadap Kinerja Bank Umum Syariah di Indonesia Periode 2012-2018 - Raden Ai Lutfi Hidayat (EkoPreneur, 2020)
The main problem in this research is the slowdown in the growth of Islamic banking in Indonesia. This is thought to be caused by the soundness of the banks themselves and the decline in banking performance. This Study selects the dependent variable of the performance of Islamic banking, namely the ratio of Financing to Deposit Ratio (FDR) which represents the level of liquidity, and Return on Assets (ROA) which represents the profit of Islamic banking. As for the independent variable, this study examines financial ratio which is included in the bank health assessment ratuis according to the Bank Indonesia version which refers to the elements of Capital, Assets, Quality, Management, Earnings, Liquidity, and Sensitivity, Shile in this study applying financial ratios commonly used to measure the financial performance of banks, including Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), Net Interest Margin (NIM) in conventional banks, Net Operation Margin (NOM) in Islamic banks, Non Performing Loans (NPL) in conventional banks and Non-Performing Financing (NPF) in Islamic banks. Therefore, it is necessary to re-examine the consistency of these variables in influencing banking performance, especially Islamic banking in Indonesia. The method used in this research is panel data regression analysis. This method is also used to obtain valid and reliable data so that it can be developed as the knowledge that can be used to understand, solve and anticipate problems in organizations, especially sharia taxis. The purpose of this study was to determine and analyze the effect of the soundness ratio of Islamic banking as measured by bank health ratios, namely CAR, NPF, BOPO, and NOM on Islamic Banking Financial Performance as proxied on the level of bank profit or profitability (ROA) and the level of liquidity (FDR). The results of this study, CAR has a positive effect on ROA. Meanwhile, FRD CAR has a negative effect. NPF has a negative effect on ROA and FDR. NOM has a positive effect on ROA. Meanwhile, For FDR NOM has a negative effect. BOPO has a negative effect on ROA and FDR. Keywords: Islamic Banking, CAR, NPF, BOPO, NOM, ROA, FDR.